مكافحة الفساد المالي والإداري من المنظورين الشرعي والقانوني - علي, جواد فقي; محمد, ناهدة عبد الغني (Sulaimani Journal for Humanities, 2018)
The strive of financial and administrative corruption is represents the problem of the age, and it’s a widespread disease in many society and a phenomenon that all the stats are suffer from, although its differ from a society to another and from a state to another . In this research the researchers take the phenomenon of financial and administrative corruption and ways of treat it from both legitimate and legal perspectives. The study of this subject is requires to distribute its scientific object into two sections :- The first:- dedicated to demonstrate the concept of financial and administrative corruption and its causes ,portrays, aspects and types. The second:-dedicated to study financial and administrative corruption from both legitimate and legal perspectives. Research concludes to mention the most important results and recommendations.